2023
DOI: 10.1111/hae.14737
|View full text |Cite
|
Sign up to set email alerts
|

Screening for subclinical synovial proliferation in haemophilia: A systematic review and meta‐analysis comparing physical examination and ultrasound

Abstract: Introduction:Ultrasound is increasingly used as addition to physical examination for detection of subclinical joint changes in haemophilia. However, the added value of ultrasound to physical examination for detecting synovial proliferation is not fully established. Aim:To determine the diagnostic accuracy of swelling at physical examination for ultrasound-detected synovial proliferation in haemophilia. Methods: PubMed and EMBASE were searched up to 2 August 2022. Studies reporting original data on occurrence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Synovial changes not meeting the criteria above were classified as inactive (fibrotic) subclinical synovial proliferation. 29 The annualised joint bleeding rate over 5 years was 0.6 (0.2-1.1). Active (22%) and inactive subclinical synovial proliferation (22%) were both prevalent in this cohort.…”
Section: Joint Assessmentmentioning
confidence: 94%
See 3 more Smart Citations
“…Synovial changes not meeting the criteria above were classified as inactive (fibrotic) subclinical synovial proliferation. 29 The annualised joint bleeding rate over 5 years was 0.6 (0.2-1.1). Active (22%) and inactive subclinical synovial proliferation (22%) were both prevalent in this cohort.…”
Section: Joint Assessmentmentioning
confidence: 94%
“…Another recent cross-sectional study by van Bergen et al, 29 which consecutively included patients with severe haemophilia A, aged 16 years and older, born after 1969, who had access to prophylaxis and were treated at the VanCreveldkliniek (UMC Utrecht, the Netherlands), reported the prevalence of subclinical synovial proliferation on US in the studied patient cohort to be 43%. The authors also proposed two subtypes of subclinical synovial proliferation in this study:…”
Section: Joint Assessmentmentioning
confidence: 96%
See 2 more Smart Citations
“…Globally, 17%-84% of PwH have reported chronic pain, although definitions of chronic pain vary amongst studies. 25 Subclinical joint bleeding has also been detected in younger and older PwH on prophylaxis, 26 and a recent study amongst PwH who were highly adherent to prophylaxis identified that only two-thirds of 97 children and one-third of 176 adults were bleed-free. 27 The influence of age on the clinical profile of pain also warrants consideration, as adults who commenced secondary or tertiary prophylaxis may live with more severe arthropathy, longstanding chronic pain and physical dysfunction compared to younger PwH on primary prophylaxis.…”
Section: Pain Is a Complex Comorbidity In The Ageing Haemophilic Popu...mentioning
confidence: 99%